Peran taman baca masyarakat Pagon Sinau dalam edukasi literasi anak di Dusun Jayan - Aris Purwanto; Sri Lestari (Jurnal Ilmiah Psikologi Terapan, 2020)
Objectives: The purpose of this research was to describethe role of literacy education conducted by TBM Panggon Sinau to children.Method: The qualitative research method is used through case studies where data is collected through interviews, observation and documentation. This study involves 4 parties with each represented by two informants: Activist of the IMM, Managers of TBM Panggon Sinau, local government in Jayan village, Parents whose children. The data was analyzed using thematic analysis. The validity of the data is achieved by using triangulation methods.Findings: Research results showed the children's literacy education is carried out through the provision of infrastructure anda variety of activities to increase interest in community library.Conclusions: The community interpreted positively the activities carried out by community reading parks for their children. The existence of TBM is able to build a collective attitude of the community to be aware of the importance of reading.Barriers experienced by TBM with regards to the lack of Central Government's role in the development of TBM and lack of related knowledge in administering community library.